X-ray diffraction and Density Functional Theory based structural analyses of 2-phenyl-4-(prop-2-yn-1-yl)-1,2,4-triazolone - Somagond, Shilpa Mallappa; Mavazzan, Ahmedraza; Madar, Suresh Fakkirappa; Sannaikar, Madivalagouda; Kumar, Shankar Madan; Inamdar, Sanjeev Ramchandra; Nesaragi, Aravind Raviraj; Dasappa, Jagadeesh Prasad; Kamble, Ravindra Ramappa (European Journal of Chemistry, 2021)
This study is composed of X-ray diffraction and Density Functional Theory (DFT) based molecular structural analyses of 2-phenyl-4-(prop-2-yn-1-yl)-2,4-dihydro-3H-1,2,4-triazol-3-one (2PPT). Crystal data for C11H9N3O: Monoclinic, space group P21/c (no. 14), a = 7.8975(2) Å, b = 11.6546(4) Å, c = 11.0648(3) Å, β = 105.212(2)°, V = 982.74(5) Å3, Z = 4, T = 296.15 K, μ(MoKα) = 0.091 mm-1, Dcalc = 1.346 g/cm3, 13460 reflections measured (5.174° ≤ 2Θ ≤ 64.72°), 3477 unique (Rint = 0.0314, Rsigma = 0.0298) which were used in all calculations. The final R1 was 0.0470 (I > 2σ(I)) and wR2 was 0.1368 (all data). The experimentally determined data was supported by theoretically optimized calculations processed with the help of Hartree-Fock (HF) technique and Density Functional Theory with the 6-311G(d,p) basis set in the ground state. Geometrical parameters (Bond lengths and angles) as well as spectroscopic (FT-IR, 1H NMR, and 13C NMR) properties of 2PPT molecule has been optimized theoretically and compared with the experimentally obtained results. Hirshfeld surface analysis with 2D fingerprinting plots was used to figure out the possible and most significant intermolecular interactions. The electronic characterizations such as molecular electrostatic potential map (MEP) and Frontier molecular orbital (FMO) energies have been studied by DFT/B3LYP approach. The MEP imparted the detailed information regarding electronegative and electropositive regions across the molecule. The HOMO-LUMO energy gap as high as 5.3601 eV was found to be responsible for the high kinetic stability of the 2PPT.